Central American monetary union - Young, John Parke; United States ([Guatemala] : U.S. Dept. of State, Agency for International Development, Regional Office, Central American and Panama Affairs, 1965)
This report discusses the problems, and measures which need to be taken in order to establish an effective monetary union within among the Central American countries..
Includes bibliographical references: p. [249]-254.
usc 07/11/2018
Loans
Keywords: Currency question; Monetary unions